2022
DOI: 10.1038/s41420-022-01149-4
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia-induced METTL3 downregulation facilitates MGLL-mediated lipolysis of adipocytes in OSAS

Abstract: Intermittent hypoxia (IH) is the core pathological feature of obstructive sleep apnea syndrome (OSAS), and insulin resistance (IR) is the most common metabolic complication of OSAS. Studies have shown that the levels of free fatty acids (FFAs), which are mainly released from adipocytes by lipolysis, are elevated in OSAS and play an important role in the development of IR. However, whether and how IH regulates adipocyte lipolysis in OSAS is not clear. Here, we revealed that the apnea hypopnea index was positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…METTL3 inhibited inflammation-induced chondrocyte apoptosis and autophagy through the m6A/YTHDF1/Bcl2 signaling pathway [77]. mRNA through the downregulation of METTL3 [78]. Moreover, OSA is significantly correlated with the development of lung carcinoma.…”
Section: Role Of M6a Methylation In Oamentioning
confidence: 95%
See 1 more Smart Citation
“…METTL3 inhibited inflammation-induced chondrocyte apoptosis and autophagy through the m6A/YTHDF1/Bcl2 signaling pathway [77]. mRNA through the downregulation of METTL3 [78]. Moreover, OSA is significantly correlated with the development of lung carcinoma.…”
Section: Role Of M6a Methylation In Oamentioning
confidence: 95%
“…Furthermore, patients with severe OSA showed dysregulated expression levels of m6A regulators, including HNRNPA2B1, KIAA1429, ALKBH5, YTHDF2, FMR1, IGF2BP1, and IGF2BP3 [97]. IH is a major feature of OSA that promotes lipolysis and the release of FFAs by significantly reducing the levels of m6A‐modified monoacylglycerol lipase (MGLL) mRNA through the downregulation of METTL3 [78]. Moreover, OSA is significantly correlated with the development of lung carcinoma.…”
Section: Association Between M6a Methylation and Osamentioning
confidence: 99%
“…An in vitro experiment showed that large lipid droplets accumulate in Mettl3-knockout cells via suppression of the mRNA and protein expression of uncoupling protein 1 (UCP1), PPARG coactivator 1 alpha (PCG-1a/PPARGC1A), PPARg, and PR/ SET domain 16 (PRDM16). A recent study on IR in obstructive sleep apnea syndrome showed that downregulation of Mettl3 increased the TG levels, which released FFAs, upregulated glycerol, inhibited glucose utilization in the other organs, and induced IR (60). Since the IR induced by obstructive sleep apnea syndrome is similar to the IR pathogenesis in T2D, this study was included in our review.…”
Section: Adipose Tissuementioning
confidence: 99%